Towards the Development of Anticancer Drugs from Andrographolide: Semisynthesis, Bioevaluation, QSAR Analysis and Pharmacokinetic Studies - Hazra, Abhijit; Mondal, Chanchal; Chakraborty, Debanjana; K. Halder, Amit; P. Bharitkar, Yogesh; K. Mondal, Susanta; Banerjee, Sukdeb; Jha, Tarun; B. Mondal, Nirup (Current Topics in Medicinal Chemistry, 2015)
Isolation of andrographolide from Andrographis paniculata, preparation of a library of derivatives via 1,3-dipolar cycloaddition of andrographolide with azomethine ylides generated from isatin derivatives or acenaphthoquinone and seconday α-amino acids, evaluation of the anticancer potential of the products, quantitative structure activity relationship studies and pharmacokinetic parameter determination have been described. 2D QSAR studies revaled that steric effects and van der Waals interactions play major roles in the determination of antiproliferative activity of these derivatives. 3D QSAR study predicted that the benzyl substitution at N20 position may be important for higher steric interaction. Pharmacokinetic studies with two most potent analogues revealed moderate chemical stability but poor aqueous solubility, metabolic stability and permeability with significant CYP3A4 inhibition.
Keywords: 2D and 3D QSAR